2014
DOI: 10.1007/s12325-014-0164-2
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide for the Treatment of Type 2 Diabetes Mellitus: A Meta-analysis of Randomized Placebo-Controlled Trials

Abstract: Liraglutide had greater hypoglycemic, weight-reducing and systolic blood pressure-lowering effects than placebo. However, there were more adverse events in the treatment with liraglutide. It is suggested that additional well-designed, large, studies be conducted to further support the use of liraglutide and provide objective guidance for clinical application of liraglutide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
0
20
0
3
Order By: Relevance
“…Skeletal muscle index (SMI) was calculated as the following: SMI = (appendicular non-fat mass, kg) divided by height (m) 2 . Body fat (%) was calculated by the whole body fat mass divided by body weight.…”
Section: Efficacy and Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle index (SMI) was calculated as the following: SMI = (appendicular non-fat mass, kg) divided by height (m) 2 . Body fat (%) was calculated by the whole body fat mass divided by body weight.…”
Section: Efficacy and Safetymentioning
confidence: 99%
“…reductions in body weight and blood pressure [1][2][3]. In addition, it is reported that liraglutide could reduce visceral fat in parallel with improvement of glycemic control [4,5].…”
mentioning
confidence: 99%
“…68 It has been associated with an increase in pulse rate. 7,8 To assess the long-term effects of liraglutide on cardiovascular outcomes and other clinically important events, the Liraglutide Effect and Action in Diabetes: Evaluation of Cardiovascular Outcome Results (LEADER) trial was initiated in 2010. 9 …”
mentioning
confidence: 99%
“…Только для лираглутида, помимо эффективного контроля углеводного обмена (снижения уровня HbA 1c , глюкозы крови натощак и постпрандиальной глюкозы), установлены множе-ственные плеотропные эффекты, включающие зна-чимое снижение массы тела в основном за счет вис-церального жира, повышенного АД, положительное влияние на липидный спектр крови, и нефропротек-тивное действие [19][20][21][22][23][24]. С целью оценки долгосроч-ных эффектов лираглутида в отношении сердечно-сосудистых исходов и прочих клинически значимых событий, согласно требованиям FDA, в 2010г было начато исследование LEADER ® (Liraglutide Effect and Action in Diabetes: Evaluation of Cardiovascular Outcome Results) [24].…”
unclassified